The Impact of Corporate Social Responsibility Disclosure on Profitability (Roa): A Study on Manufacturing Companies In Asean–5 Countries 2019-2023 - Marsandha Azzahra Paramita; Harjum Muharam (Diponegoro Journal of Management, 2026)
This research aims to analyze the impact Corporate Social Responsibility (CSR) has on the Profitability of manufacturing companies across the ASEAN-5 countries during the 2019-2023 period. The variables identified are dependent variable Profitability, measured through Return on Assets (ROA), and independent variable, Corporate Social Responsibility (CSR) calculated according to the GRI standards. Samples used to conduct this research were collected through purposive sampling from 87 manufacturing companies listed in Indonesia Stock Exchange (IDX), Bursa Malaysia, Singapore Exchange (SGX), Stock Exchange of Thailand (SET) and Philippines Stock Exchange (PSE) during 2019-2023 as data required to analyze the calculation of variables in this study. Research data were obtained from companies annual or sustainability report and the Bloomberg terminal. The data was examined through multiple linear regression analysis and Hypothesis Testing in EViews version 12. This concludes the relationship indicated between the variable CSR and Profitability (ROA) results in a significant positive impact. Thus, hypothesis for this study is accepted. Furthermore, this study incorporates control variables SIZE, AGE, and GROWTH. Findings indicates a positive significant impact GROWTH has on ROA, while others show insignificancy.